1999
DOI: 10.1117/12.339133
|View full text |Cite
|
Sign up to set email alerts
|

<title>Type III photosensitization: attempt for quantification and a way toward new sensitizers</title>

Abstract: Earlier results studying the effect of excited triplet photosensitizer on the zymosan-stimulated and luminol-dependent chemiluminescence of macrophages have been quantitatively re-evaluated and rate constant data indicate that the effect is due to triplet-doublet interactions between sensitizer and free radicals generated.Such interactions, named Type III mechanism, compete with Type I and Type II mechanisms depending on the experimental environment. This suggestion resulted in the synthesis of new sensitizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several research groups have reported results on the PDT enhancing activities of certain antioxidant molecules, such as ascorbate,104 3(2)-tetra-butyl-4-hydroxyanisole,105 epigallocatechin-3-gallate,106 α-tocopherol,107 and trolox ([±]-6-hydroxyl-2, 5, 7, 8-tetramethyl chromane-2-carboxylic acid, a water soluble vitamin E analogue) 108. Based on these intriguing results, some antioxidant carrier sensitizers (ACSs) which conjugated PSs and antioxidants together were designed and studied for their photodynamic anticancer109 and antibacterial activities 110. It was noted that the PDT effect of such ACSs is based on the so called type III (or MTO) mechanism which increases the singlet oxygen production via inhibition of the interaction between triplet excited PS and native free radicals 109…”
Section: Pdtmentioning
confidence: 99%
“…Several research groups have reported results on the PDT enhancing activities of certain antioxidant molecules, such as ascorbate,104 3(2)-tetra-butyl-4-hydroxyanisole,105 epigallocatechin-3-gallate,106 α-tocopherol,107 and trolox ([±]-6-hydroxyl-2, 5, 7, 8-tetramethyl chromane-2-carboxylic acid, a water soluble vitamin E analogue) 108. Based on these intriguing results, some antioxidant carrier sensitizers (ACSs) which conjugated PSs and antioxidants together were designed and studied for their photodynamic anticancer109 and antibacterial activities 110. It was noted that the PDT effect of such ACSs is based on the so called type III (or MTO) mechanism which increases the singlet oxygen production via inhibition of the interaction between triplet excited PS and native free radicals 109…”
Section: Pdtmentioning
confidence: 99%
“…This was based on the fact that when inhibitor molecules react with free radicals and decrease the reactivity of the latter (“stabilizing” the radical into a molecule) the efficacy of ground state oxygen in the competition for the triplet sensitizer is increased and thus the contribution of the singlet oxygen–mediated pathway is increased (in special cases, when photodynamic treatment itself generates free radicals contributing to the treatment, inhibitor molecules might reduce the extent of the overall effect that might occur at a low oxygen concentration). Two compounds, antioxidant carrier sensitizer‐2 (ACS‐2) and antioxidant carrier sensitizer‐3 (ACS‐3), have been devised, synthesized and tested, with promising results, in preliminary experiments in tumor‐bearing mice as photodynamic anticancer agents (23).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative MOAs to the type I and type II pathways have been reported in literature despite a lack of consensus regarding the definition of oxygen-independent mechanisms. , A modified type I mechanism, called type III, has been described based on an interaction between the PS in its first excited triplet state and doublet free radicals with diffusion-controlled rate constants. Other reports of oxygen-independent mechanisms involve the generation of toxic photoproducts from upper excited triplet states, photoinduced electron transfers leading to cycloaddition reactions, , and structural changes upon excitation that allow binding to intracellular targets. , These properties currently preclude therapeutic deployment. Additional agents for phototherapy undergoing photoredox catalysis have been reported recently. , …”
Section: Introductionmentioning
confidence: 99%